37 NEW ORLEANS SENIORS ON POLYPHARMACY: THE IMPACT OF INTERVENTION ON ADVERSE DRUG REACTIONS AND COST OF MEDICATIONS. Issue 1 (1st January 2007) - Kumar, P.; Elshatory, K. M.; Vital, C.; Kamboj, S.
Abstract : Purpose: According to published reports, approximately 50% of New Orleans seniors consume five or more medications on a long term basis (polypharmacy). Furthermore, polypharmacy increases the risk of adverse drug reactions (ADRs) and contributes to the high cost of medications. The goal of this pilot study was to apply an intervention strategy designed to stop inappropriate medication use and to evaluate its impact on the risk of ADRs and the cost of medications. Methods: Nine patients, 66-83 years of age, who met the definition of polypharmacy were evaluated. Patients with HIV, malignancy, transplanted organs, and advanced CHF were excluded. We used a medication appropriate index to stop inappropriate medications with the approval of the primary care physician. The ADRs, Mini-Mental Status Examination (MMSE), and monthly cost of medications were recorded before and after intervention. Results: The mean number of medications was 13.5 medications daily before and was decreased to 7.3 medications daily after intervention. The mean cost of medications decreased from 352 dollars monthly before intervention to 128 dollars monthly after intervention ( p < .001). The mean number of ADRs decreased from 3.0 before to 0.3 after intervention ( p = .0005). The most common side effect was dizziness due to orthostatic hypotension caused by metoprolol and hydrochlorothiazide. The most serious side effect was angioedema secondary to captopril. The MMSE scores improved from 25.5 before to 28.1 after intervention ( p = .04). Conclusion: The seniors on polypharmacy can be benefited by stopping inappropriate medications, resulting in decreased ADRs and reduced cost of medications.